Efektivitas Isometric Handgrip Exercise dan Slow Deep Breathing Exercise terhadap Perubahan Tekanan Darah pada Penderita Hipertensi - Juli Andri; Agung Waluyo; Wati Jumaiyah; Dhea Nastashia (Jurnal Keperawatan Silampari, 2018)
This study aims to identify the effectiveness of isometric handgrip exercise and slow deep breathing exercise on changes in blood pressure in patients with hypertension. Quasi experimental research design with a two group pretest posttest research design on 32 respondents. The results showed that there was a change in systolic and diastolic blood pressure after an Isometric Handgrip Exercise intervention (t = 8,279, p = 0,000), (t = 6,154, p = 0,000), and changes in systolic and diastolic blood pressure after a slow deep intervention was given breathing exercise (t = 3,632, p = 0,002), (t = 4,226, p = 0,001). Conclusion, both isometric handgrip exercise and slow deep breathing exercise can significantly reduce systolic and diastolic blood pressure in hypertensive patients. Keywords: Hypertension, Isometric Handgrip Exercise, Slow Deep Breathing Exercise, Blood Pressure